Function of the HYDROXYCINNAMOYL-CoA:SHIKIMATE HYDROXYCINNAMOYL TRANSFERASE is evolutionarily conserved in embryophytes. Issue 8 (6th February 2021) - Kriegshauser, Lucie; Knosp, Samuel; Grienenberger, Etienne; Tatsumi, Kanade; Gütle, Desirée D; Sørensen, Iben; Herrgott, Laurence; Zumsteg, Julie; Rose, Jocelyn K C; Reski, Ralf; Werck-Reichhart, Danièle; Renault, Hugues
Abstract: The plant phenylpropanoid pathway generates a major class of specialized metabolites and precursors of essential extracellular polymers that initially appeared upon plant terrestrialization. Despite its evolutionary significance, little is known about the complexity and function of this major metabolic pathway in extant bryophytes, which represent the non-vascular stage of embryophyte evolution. Here, we report that the HYDROXYCINNAMOYL-CoA:SHIKIMATE HYDROXYCINNAMOYL TRANSFERASE ( HCT ) gene, which plays a critical function in the phenylpropanoid pathway during seed plant development, is functionally conserved in Physcomitrium patens (Physcomitrella), in the moss lineage of bryophytes. Phylogenetic analysis indicates that bona fide HCT function emerged in the progenitor of embryophytes. In vitro enzyme assays, moss phenolic pathway reconstitution in yeast and in planta gene inactivation coupled to targeted metabolic profiling, collectively indicate that P. patens HCT (PpHCT), similar to tracheophyte HCT orthologs, uses shikimate as a native acyl acceptor to produce a p -coumaroyl-5- O -shikimate intermediate. Phenotypic and metabolic analyses of loss-of-function mutants show that PpHCT is necessary for the production of caffeate derivatives, including previously reported caffeoyl-threonate esters, and for the formation of an intact cuticle. Deep conservation of HCT function in embryophytes is further suggested by the ability of HCT genes from P. patens and the liverwort Marchantia polymorpha to complement an Arabidopsis thaliana CRISPR/Cas9 hct mutant, and by the presence of phenolic esters of shikimate in representative species of the three bryophyte lineages. Abstract : The catalytic properties and physiological function of a key enzyme in the phenylpropanoid pathway were conserved across the 500 million years of embryophyte evolution.